2016
DOI: 10.1038/srep27884
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability of poly(lactic-co-glycolic acid) after femtosecond laser irradiation

Abstract: Biodegradation is a key property for biodegradable polymer-based tissue scaffolds because it can provide suitable space for cell growth as well as tailored sustainability depending on their role. Ultrashort pulsed lasers have been widely used for the precise processing of optically transparent materials, including biodegradable polymers. Here, we demonstrated the change in the biodegradation of a poly(lactic-co-glycolic acid) (PLGA) following irradiation with femtosecond laser pulses at different wavelengths. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 28 publications
(59 reference statements)
1
20
0
Order By: Relevance
“…In crystalline polymers, rapid melt and quenching should have an effect on the crystallinity and/or crystal structure since the high cooling rate limits the time available for crystal formation and growth. The only measurements on the effect of femtosecond laser irradiation on polymer crystallinity were performed on amorphous PLA where, as expected, crystallinity was not induced during machining [22,23].…”
Section: Introductionmentioning
confidence: 84%
“…In crystalline polymers, rapid melt and quenching should have an effect on the crystallinity and/or crystal structure since the high cooling rate limits the time available for crystal formation and growth. The only measurements on the effect of femtosecond laser irradiation on polymer crystallinity were performed on amorphous PLA where, as expected, crystallinity was not induced during machining [22,23].…”
Section: Introductionmentioning
confidence: 84%
“…Femtosecond laser processing of biodegradable polymers has advantages in 3D precise processing; however, detailed studies on the effects of femtosecond laser irradiation on the degradable property are limited to a few cases. Our group found different degradation rates of the biodegradable polymer after femtosecond laser ablation, which depends on the laser wavelength [40]. Figure 3 shows a comparison of laser ablation craters on a PLGA surface at different times after irradiation with 800-nm and 400-nm femtosecond laser pulses.…”
Section: Degradable Property After Laser Irradiationmentioning
confidence: 98%
“…The degradation rate of a biodegradable polymer after laser irradiation has been explained by the decrease in crystallinity associated with surface melting, and in molecular weight owing to the photolysis of chemical bonds. Because PLGA is a polymer with less crystallinity, with the wavelength of 400 nm, the significant acceleration of the biodegradation in the case of PLGA [40] is attributable to the decrease in molecular weight induced by the chemical bond dissociation rather than the change in crystallinity. the latter has a more significant influence [56].…”
Section: Degradable Property After Laser Irradiationmentioning
confidence: 99%
“…Undoubtedly more examples of in vivo applications of photoporation will follow in the near future. Here, it will be of interest to develop biocompatible sensitizing materials because of the toxicity concerns in relation to the in vivo usage of colloidal NPs [163]. In a recent report, it was, for instance, shown that VNBs can be formed by irradiating hemozoin crystals (malaria related organic crystals) in the blood circulation with laser light [164].…”
Section: Perspectives and Conclusionmentioning
confidence: 99%